Characterization of planetary regolith simulants for the research and development of space resource technologies - Long-Fox, Jared M.; Britt, Daniel T. (Frontiers in Space Technologies, 2023)
Human planetary exploration and colonization efforts are reliant on the ability to safely interact with planetary surfaces and to leverage local regolith as a resource. The high-cost and risk-intensive nature of establishing planetary infrastructure and resource utilization facilities necessitates risk reduction through laboratory-based research and development of space resource acquisition, processing, and extraction technologies using appropriate, well-characterized, mineral-based regolith simulants. Such simulants enable the planetary exploration and resource utilization communities to test large-scale technologies and methodologies for a relatively low cost as an alternative to scarce and expensive returned samples. The fidelity of a regolith simulant for any application is, in part, determined by the mineralogical composition and particle size distribution. The importance of composition is well established for in situ resource utilization studies sensitive to geochemical properties but tends to be ignored in studies concerned with physical properties. Neglecting to consider mineralogy reduces the fidelity of a simulant since each mineral species has its own unique grain density, preferred grain geometry, and intergranular forces, all of which affect the physical properties of the simulant (e.g., shear strength, bearing strength, bulk density, thermal and electrical properties, magnetic properties). Traditionally, regolith simulants have been limited in quantity and availability; Exolith Lab remedies these problems by designing simulants in a constrained maximization approach to fidelity relative to cost, material availability, and safety. Exolith Lab simulants are designed to approximate the mineralogy and particle size ranges of the planetary regolith being simulated, with composition constrained by remote sensing observations and/or returned sample analyses. With facilities and equipment capable of high-volume simulant production, Exolith Lab offers standard simulants in bulk that are readily available for purchase and shipment. This work reviews the production methods, equipment, and materials used to create Exolith Lab simulants, provides compositional data, particle size data, and applications for each standard lunar, Martian, and asteroid simulant that Exolith Lab offers.